A Concept Analysis of Resilience Integrating Genetics. (2nd November 2017) - Niitsu, Kosuke; Houfek, Julia F.; Barron, Cecilia R.; Stoltenberg, Scott F.; Kupzyk, Kevin A.; Rice, Michael J.
ABSTRACT: Although clinicians and researchers are interested in the phenomenon of resilience, there is no agreed-upon definition of resilience. Scientific evidence suggests that resilience is influenced by intrapersonal (e.g. personality traits) and environmental (e.g. social support) variables. A concept analysis was conducted to better understand the meaning of resilience. In this analysis, the antecedent of resilience was a potentially traumatic event ; the defining attributes were ego-resiliency, emotion regulation, social support, and heredity ; and the consequences were none to mild psychopathological symptoms and positive adaptation . This analysis can help nurses better understand resilience and its relationships to both intrapersonal and environmental variables.